PENINGKATAN KREATIVITAS BELAJAR MATEMATIKA MELALUI PENDEKATAN KONTEKSTUAL (CTL) - Dewi Azizah (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2012)
The  purposes  of  the    research  were,  first,  to  increase  the  students’  creativity  of  learning mathematic and, second, to improve students’ learning achievement by using contextual approach. The research was a collaborative achievement research between the writer, the  mathematic teacher and headmaster. The subject of the research were the  eighth  grade  student  of  SMP  Muhammadiyah  10  Surakarta.  The  qualitative descriptive  data  were  than  analyzed  through  the  use  of  alur  method.  The  results showed  the  contextual  approach  could  improve  the  students’  creativity  and achievement significantly. The students’ creativity got improved ≥65% and students’ achievement rose from 48.1% to 68.9%. Keywords: creativity, contextual, achievement